Prostate Cancer Care Before and After Medicare Eligibility - Marco D. Huesch MBBS, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2016)
Prior studies suggest Medicare eligibility confers significant and substantial reductions in mortality and beneficial increases in health service utilization. We compared 13 882 patients diagnosed with prostate cancer at ages 63 to 64 years with 14 774 patients diagnosed at ages 65 to 66 (controls) in 2004 to 2007. Compared with controls, patients diagnosed with prostate cancer before Medicare eligibility had no statistically significant or meaningful differences in cancer stage, time to treatment, or type of treatment.